AQP1-Containing Exosomes in Peritoneal Dialysis Effluent As Biomarker of Dialysis Efficiency - Simone Corciulo; Maria Celeste Nicoletti; Lisa Mastrofrancesco; Serena Milano; Maria Mastrodonato; Monica Carmosino; Andrea Gerbino; Roberto Corciulo; Roberto Russo; Maria Svelto; Loreto Gesualdo; Giuseppe Procino (Cells, 2019)
The water channel Aquaporin 1 (AQP1) plays a fundamental role in water ultrafiltration during peritoneal dialysis (PD) and its reduced expression or function may be responsible for ultrafiltration failure (UFF). In humans, AQP1 is expressed in the endothelium of the peritoneal capillaries but its expression in mesothelial cells (MC) and its functional role in PD is still being debated. Here, we studied a cohort of 30 patients using PD in order to determine the presence of AQP1 in peritoneal biopsies, AQP1 release in the PD effluent through exosomes and the correlation of AQP1 abundance with the efficiency of peritoneal ultrafiltration. The experiments using immunofluorescence showed a strong expression of AQP1 in MCs. Immunoblotting analysis on vesicles isolated from PD effluents showed a consistent presence of AQP1, mesothelin and Alix and the absence of the CD31. Thus, this suggests that they have an exclusive mesothelial origin. The immunoTEM analysis showed a homogeneous population of nanovesicles and confirmed the immunoblotting results. Interestingly, the quantitative analysis by ELISA showed a positive correlation between AQP1 in the PD effluent and ultrafiltration (UF), free water transport (FWT) and Na-sieving. This evidence opens the discussion on the functional role of mesothelial AQP1 during PD and suggests that it may represent a potential non-invasive biomarker of peritoneal barrier integrity, with predictive potential of UFF in PD patients.